Evaluation of Vasopressor Exposure and Mortality in Patients With Septic Shock*. Issue 10 (October 2020) - Roberts, Russel J.; Miano, Todd A.; Hammond, Drayton A.; Patel, Gourang P.; Chen, Jen-Ting; Phillips, Kristy M.; Lopez, Natasha; Kashani, Kianoush; Qadir, Nida; Cairns, Charles B.; Mathews, Kusum; Park, Pauline; et al.
Abstract : Objectives: The objectives of this study were to: 1) determine the association between vasopressor dosing intensity during the first 6 hours and first 24 hours after the onset of septic shock and 30-day in-hospital mortality; 2) determine whether the effect of vasopressor dosing intensity varies by fluid resuscitation volume; and 3) determine whether the effect of vasopressor dosing intensity varies by dosing titration pattern. Design: Multicenter prospective cohort study between September 2017 and February 2018. Vasopressor dosing intensity was defined as the total vasopressor dose infused across all vasopressors in norepinephrine equivalents. Setting: Thirty-three hospital sites in the United States ( n = 32) and Jordan ( n = 1). Patients: Consecutive adults requiring admission to the ICU with septic shock treated with greater than or equal to 1 vasopressor within 24 hours of shock onset. Interventions: None. Measurements and Main Results: Out of 1, 639 patients screened, 616 were included. Norepinephrine (93%) was the most common vasopressor. Patients received a median of 3, 400 mL (interquartile range, 1, 851–5, 338 mL) during the 24 hours after shock diagnosis. The median vasopressor dosing intensity during the first 24 hours of shock onset was 8.5 μg/min norepinephrine equivalents (3.4–18.1 μg/min norepinephrine equivalents). In the first 6 hours, increasing vasopressor dosing intensity was associated with increased odds ratio of 30-day in-hospital mortality, with the strength of association dependent on concomitant fluid administration. Over the entire 24 hour period, every 10 μg/min increase in vasopressor dosing intensity was associated with an increased risk of 30-day mortality (adjusted odds ratio, 1.33; 95% CI, 1.16–1.53), and this association did not vary with the amount of fluid administration. Compared to an early high/late low vasopressor dosing strategy, an early low/late high or sustained high vasopressor dosing strategy was associated with higher mortality. Conclusions: Increasing vasopressor dosing intensity during the first 24 hours after septic shock was associated with increased mortality. This association varied with the amount of early fluid administration and the timing of vasopressor titration. Abstract : Supplemental Digital Content is available in the text.